2014
DOI: 10.1007/s10555-014-9538-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular therapies in ovarian cancer: moving beyond anti-VEGF approaches

Abstract: Resistance to chemotherapy is among the most important issues in the management of ovarian cancer. Unlike cancer cells, which are heterogeneous as a result of remarkable genetic instability, stromal cells are considered relatively homogeneous. Thus, targeting the tumor microenvironment is an attractive approach for cancer therapy. Arguably, anti-vascular endothelial growth factor (anti-VEGF) therapies hold great promise, but their efficacy has been modest, likely owing to redundant and complementary angiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 212 publications
1
85
0
Order By: Relevance
“…CNA alterations may modulate the SLC9A1 expression by endothelin-1 and epidermal growth factor, complementing reports involving endothelin-1 and endothelin receptor A in this type of cancer [40] and endothelin-1 in combination with -arrestin-1 activation increasing chemoresistance [41]. Equally, activation of epidermal growth factor/epidermal growth factor receptor signalling is involved in higher angiogenesis [42] and resistance to paclitaxel [43] showing that inhibition of NHE1 activity results in a higher sensitivity to paclitaxel in breath cancer [47]. Thus, strategies to control NHE1 expression and activity in patients with ovary cancer could be of benefit reducing the adverse patient's outcome of this disease.…”
mentioning
confidence: 57%
“…CNA alterations may modulate the SLC9A1 expression by endothelin-1 and epidermal growth factor, complementing reports involving endothelin-1 and endothelin receptor A in this type of cancer [40] and endothelin-1 in combination with -arrestin-1 activation increasing chemoresistance [41]. Equally, activation of epidermal growth factor/epidermal growth factor receptor signalling is involved in higher angiogenesis [42] and resistance to paclitaxel [43] showing that inhibition of NHE1 activity results in a higher sensitivity to paclitaxel in breath cancer [47]. Thus, strategies to control NHE1 expression and activity in patients with ovary cancer could be of benefit reducing the adverse patient's outcome of this disease.…”
mentioning
confidence: 57%
“…Two weeks after tumor cell injection, ovarian cancer-bearing mice were the vessel system for improved drug delivery (38)(39)(40)(41). However, several clinical trials in cancer patients have demonstrated that agents targeting VEGF family members convey a progression-free survival advantage but rarely an overall survival advantage, possibly because other potent proangiogenic factors and their downstream effector molecules are present in the tumor microenvironment and endothelial cells, respectively, leading to insufficient suppression of tumor angiogenesis (1,2,42).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor vasculature plays an important role in the pathogenesis and progression of HGSC and is crucial in modulating the delivery of therapeutic agents (1). Various tumor cell-derived cytokines, including VEGFs and FGFs, are involved in HGSC pathogenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These therapies are approved for treatment of a variety of human cancers (3) and include the monoclonal anti-VEGF antibody bevacizumab (4,5) and multitargeted receptor tyrosine kinase inhibitors (6). However, in most clinical trials, these agents have only offered modest improvements in progression-free survival, without affecting overall survival (7).…”
Section: Introductionmentioning
confidence: 99%